2017
DOI: 10.1177/2156759x18780952
|View full text |Cite
|
Sign up to set email alerts
|

Protective Factors for Mental Health Concerns in Urban Middle School Students

Abstract: Addressing mental health in urban schools with youth who are often disadvantaged requires an understanding of protective individual and school contextual influences. Using hierarchical multiple regression analyses, we investigated school connectedness (SC) as a moderator between social skills (SS) and emotional/behavioral difficulties (ED/BD) among 319 urban middle school students (Grades 6-8; 65% self-identified as Black). SS levels predicted ED/BD. SC moderated the association between SS and mental health co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 53 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…Anderson-Butcher et al (2013) reported the coefficient α of 0.76 for this measure among 2,360 third to sixth graders. The coefficient α was 0.72 in another study of middle school students (Carney, Kim, et al, 2018). The scale was significantly correlated to a related CAYCI-SES subscale, peer relationships (r = 0.57).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Anderson-Butcher et al (2013) reported the coefficient α of 0.76 for this measure among 2,360 third to sixth graders. The coefficient α was 0.72 in another study of middle school students (Carney, Kim, et al, 2018). The scale was significantly correlated to a related CAYCI-SES subscale, peer relationships (r = 0.57).…”
Section: Methodsmentioning
confidence: 87%
“…Social skills, as personal assets, refer to the ability to effectively engage in social interactions (Anderson-Butcher, Amorose, Iachini, & Ball, 2013). This asset enables children to experience positive interaction with adults and peers at school (Carney, Kim, Hazler, & Guo, 2018). Social skills have been identified as a critical contributor to student success such as enhanced academic achievement (Gresham, 2016) and lower psychological distress (Segrin, McNelis, & Swiatkowski, 2016).…”
Section: Developmental Assets and Lsmentioning
confidence: 99%
“…A growing body of research has revealed school connectedness as a powerful predictor of students' achievement in academic and other essential domains (e.g., Bryan et al, 2012;Carney, Kim, et al, 2018;Lapan et al, 2014;Smith & Sandhu, 2004), but little is known about its associated factors. An additional layer of the research gap pertains to mechanisms involved in school connectedness outcomes and grade-related variabilities during early adolescence.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…A review of Liu et al the literature indicates a scarcity of information on students' school connectedness in early adolescence (i.e., elementary to early middle school stage). Most available studies tend to focus on school connectedness at the middle school level (e.g., Carney, Kim, et al, 2018;Lemberger et al, 2015;Oelsner et al, 2011), in high schools (Bryan et al, 2012), or during the transition from middle school to high school (Lester et al, 2013;Meisel & Colder, 2017). We found only one study (Lemberger & Clemens, 2012) that examined the incorporation of connectedness into school counseling interventions specifically for elementary school students from socially disadvantageous statuses.…”
mentioning
confidence: 97%
See 1 more Smart Citation